The Relationship among Self-efficacy, Metacognitive Ability and Academic Motivation with Math Performance of High School Students in Parsian - Movaghar, Mahnaz; Darman, Fariba; Gholami, Mohammad Hosein (IJRDO- Journal of Educational Research, 2017)
The purpose of this study was to determine the relationship among self-efficacy, meta-cognitive ability and academic motivation with math performance of high school students in Parsian. This research has been applied in a purposeful and descriptive way and has been correlated with research type. The statistical population of this study was all high school students in Parsian. Sample size: 150 people were selected by cluster sampling method. Measurement tools were selfefficacy questionnaire, meta-cognitive ability questionnaire and academic motivation questionnaire. The results of this research have shown that there is a significant and positive relationship between self-efficacy, metacognitive ability, academic motivation and mathematical function. Also, student’s math performance is predictable through the components of self-efficacy, metacognitive ability, and academic motivation. In total, approximately 30.3% of variance predicts students’ mathematical performance variables.